Risalah Wanita Dalam Agama dan Masyarakat Telaah Yuridis Antroplogis - Maula, Ismatul; Ida, Ida Rif’atus Sa’adah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2022)
Women are the focus of this research, which is a literature study with an anthropological juridical approach, seeing women from the perspective of religion and society. Their roles and status are often perceived as unfair. Although in the text and context, it is clear that there is no habit in the position of women. There are limits set by religion as a form of protection for women, not the other way around. This is what is interesting in this research by looking for the truth point of how women are juridically studied from the perspective of religion and how women are socially seen in the order of their roles and positions, is there really a habit in them so that justice and equality must continue to be voiced. From these questions, it comes to a conclusion that women, both in religion and in society, have the same duties and responsibilities as men. His position in religion is very important, even in Islam before his arrival women did not have social status. Islam actually came to equalize the position of women with men. Their roles and activities are also not limited as long as they do not conflict with syara`. In society, there are cultures, customs and norms that actually have noble values that must be preserved. So women in this view clearly have a high status treatise in the frame of their dignity and honor